THE EFFECT OF FIRM SIZE, PROFITABILITY, AND LIQUIDITY ON FIRM VALUE WITH CAPITAL STRUCTURE AS INTERVENING VARIABLES - Sri Hermuningsih; Teguh Santoso; Riskin Hidayat; Saizal bin Pinjaman (ZILLZELL MEDIA PRIMA, 2026)
This study aims to examine, the effect of firm size, profitability, and liquidity on firm value and capital structure as intervening variables. The focus of this study is on companies in the property and real estate sector listed on the Indonesia Stock Exchange during the period 2019 to 2023. The indicators used include profitability measured using size, Price Book Value, Return on Assets and Current Ratio, while capital structure is measured using the Debt to Equity Ratio. The sample in this study consisted of 19 companies using purposive sampling. The results of hypothesis testing show that company size, profitability, liquidity and capital structure has a positive and significant effect on firm value, company size has a positive and significant effect on capital structure, profitability has no effect on capital structure, Liquidity has a positive and significant effect on capital structure, Capital structure can mediate the relationship between firm size and firm value, while capital structure does not mediate the relationship between profitability and firm value, but capital structure mediates the relationship between liquidity and firm value.